Forcing Convection to Aggregate Using Diabatic Heating Perturbations. (9th October 2021) - Dingley, Beth; Dagan, Guy; Stier, Philip
Abstract: Tropical deep convection can aggregate into large clusters, which can have impacts on the local humidity and precipitation. Sea surface temperature (SST) gradients have been shown to organize convection, yet there has been little work done to investigate the impact of diabatic heating perturbations in the atmosphere on the aggregation of convection. Here we investigate how anomalous diabatic heating of the atmospheric column, through an idealized aerosol plume, affects the existence and mechanisms of convective aggregation in non‐rotating, global radiative‐convective equilibrium simulations. We show that the aerosol forcing has the ability to increase the degree of aggregation, especially at lower SSTs. Detailed investigation shows that the diabatic heating source incites a thermally driven circulation, forced by the shortwave perturbation. The increase in aggregation is caused in part by this circulation, and in part by the longwave heating anomalies occurring due to the surface convergence of moisture and convection. At higher SSTs, longwave feedbacks are crucial for the aggregation of convection, even with the shortwave heating perturbation. At lower SSTs, convection is able to aggregate with the shortwave perturbation in the absence of longwave feedbacks. These perturbations provide a link to studying the effects of absorbing aerosol plumes on convection, for example during the Indian monsoon season. We argue that, as there is aggregation for plumes with realistic aerosol absorption optical depths, this could be an analogue for real‐world organization in regions with high pollution. Plain Language Summary: Tropical clouds grouping together into large clusters in idealized climate models is an interesting topic of research. When this happens, the average temperature increases with more rain where the clouds are and less rain away from them. This paper looks at how we can force clouds to cluster together. We use plumes of aerosols to cause heating perturbations. We show that this causes a large‐scale circulation to develop, with warm air rising near to the plume and cold air sinking further away from it. This helps clouds to cluster together, through changes in the absorption and reflection of longwave and shortwave radiation. We highlight that real‐world pollution plumes or dust events may have similar effects on the clustering of clouds near to them. Key Points: Can increase the degree of aggregation by using a shortwave radiative heating perturbation Radiative heating perturbation incites a global thermally driven circulation Shortwave radiative heating perturbation can aggregate convection at lower sea surface temperatures, even without typically crucial longwave feedbacks